Programação de ensino em dança educativa voltada a crianças com deficiência física - Rossi, Patrícia (Universidade Federal de São Carlos, 2014)
It is possible to identify, in scientific literature, many studies involving physically disabled people and dance in different contexts (educational, rehabilitation, artistic and sports) and various purposes (pedagogical, therapeutic, performing and competitive). However, there is little research involving dance and physically disabled children in pedagogical purposes. In order to fill these gaps, this study has as its theme the development and analysis of an educational dance program with pedagogical purpose focused on physically disabled children, irrespective of etiology, and centered on the teaching process evaluation. The general objective was to investigate the effects of a teaching program in the process of learning educational dance on physically disabled children. The specific objectives were: 1) to systematize, apply, describe and evaluate an educational dance program for physically disabled children, 2) to establish evaluation criteria focused on the teaching and learning process of educational dance to be used as parameters for continued analysis, 3) to examine the physically disabled children s progress during educational dance program, 4) to verify the levels of support needed by the participants during the program; 5) to verify which aspects analyzed by the rating instrument in dance program had more or less influence on such children. The developed research had both quantitative and qualitative approaches, characterized as an experimental research of within-subject BAB design. The sample consisted of four children three males and one female with an age range between nine and fourteen, whose common characteristic is physical disability of different etiologies. The data collection instruments applied were: 1) Educational Dance Learning Follow Up Instrument ( Instrumento de Acompanhamento da Aprendizagem em Dança Educativa IAADE ), developed by the researcher and completed at the end of each session, supported by filming; and 2) field diary, containing the record of observations made by the researcher during the educational dance program. The educational dance program was developed empirically based on the theoretical approach of Rudolph Laban, considering the pedagogical perspective. The program had duration of 12 weeks, including two weekly classes of 50 minutes each, adding up to 24 sessions. Data analysis was performed quantitatively and qualitatively, based on contents analysis. The results shown by IAADE demonstrated improvement in student s dance skills during period B, while during period A the results remained unaltered, confirming that the students were able to preserve/maintain their previous acquisitions. The data obtained from the field diary showed students had intensified their interpersonal relationships, demonstrating attitudes of friendship and companionship. Regarding the Educational Dance Program, it was observed that the skills which demonstrated significant improvement were: laterality, clapping rhythm and movement, directions exploration (forward, backward and sideways) and the space levels (low, medium and high). The educational dance program for physically disabled children, centered on teaching process and with pedagogical purpose, was considered efficient with regard to the improvement of the participants related skills during the intervention phase of the program.
Keywords: Dança; Educação física adaptada; Criança; Deficiência física; Special education; Adapted physical education; Educational dance; Physical disability; Childhood; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL